Five-Year Growth of Rock Lichens in a Low-Arctic Mountain Environment, Northern Labrador - Rogerson, R.; Evans, D.; McCoy, W. (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1986)
ABSTRACTIn 1978, three lichen growth stations were established for Rhizocarpon section Rhizocarpon species and one for Alectoria miniscula in the Cirque Mountain area of the Torngat mountains. Five years later, in 1983, the lichens were remeasured. The five-year growth represented by the change in the theoretical diameter is very variable, between 0.10 and 0.54 mm per year. These rates are larger than expected and exceed rates previously determined for an eastern Arctic area, the Northern Cumberland Peninsula of Baffin Island, by more than 3 to more than 20 times. Similar rates are known for 'great period' growth outside Arctic regions. If the growth rates represent long-term growth, the ages of recessional moraines in the Torngat Mountains should be recalculated. Moraines formerly described as Late Wisconsin to mid-Holocene may be of Neoglacial age. Variability of growth rates from one individual to another precludes using these data for constructing growth curves which may be used, even locally, in lichenometric dating.